Consistent habitat preference underpins the geographically divergent autumn migration of individual Mongolian common shelducks. Issue 4 (13th November 2019) - Meng, Fanjuan; Wang, Xin; Batbayar, Nyambayar; Natsagdorj, Tseveenmyadag; Davaasuren, Batmunkh; Damba, Iderbat; Cao, Lei; Fox, Anthony D
Abstract: While many avian populations follow narrow, well-defined "migratory corridors, " individuals from other populations undertake highly divergent individual migration routes, using widely dispersed stopover sites en route between breeding and wintering areas, although the reasons for these differences are rarely investigated. We combined individual GPS-tracked migration data from Mongolian-breeding common shelduck Tadorna tadorna and remote sensing datasets, to investigate habitat selection at inland stopover sites used by these birds during dispersed autumn migration, to explain their divergent migration patterns. We used generalized linear mixed models to investigate population-level resource selection, and generalized linear models to investigate stopover-site-level resource selection. The population-level model showed that water recurrence had the strongest positive effect on determining birds' occupancy at staging sites, while cultivated land and grassland land cover type had strongest negative effects; effects of other land cover types were negative but weaker, particularly effects of water seasonality and presence of a human footprint, which were positive but weak or non-significant, respectively. Although stopover-site-level models showed variable resource selection patterns, the variance partitioning and cross-prediction AUC scores corroborated high inter-individual consistency in habitat selection at inland stopover sites during the dispersed autumn migration. These results suggest that the geographically widespread distribution (and generally rarity) of suitable habitats explained the spatially divergent autumn migrations of Mongolian breeding common shelduck, rather than the species showing flexible autumn staging habitat occupancy.